Asociación de la hipomineralización incisivo-molar con la edad y género en niños de una institución educativa pública del distrito de Ate Vitarte, en el año 2013 - Maccagno Robinson, Leia (2014)
Aims: To determine the association of molar-incisor hypomineralization with age and gender in children from a public school of Ate Vitarte district, in 2013. Materials and Methods: An descriptive, observational and transverse study in 197 children aged between 6-12 years old. Data collection was conducted by one examiner in a public school district of Ate Vitarte that performed the assessment of the severity of MIH according to criteria established by Mathu-Muju and Wright (2006). Data on gender, age and distribution pattern was also taken. Results: The prevalence of hypomineralization was 63.4%. Of these, 1.6% showed severe signs of MIH, 10.4% moderate signs and 88% mild signs. Regarding the distribution pattern, it was found that 46.4% had MIH Type I, 33.6% Type II and Type III were affected in 20%. No statistically significant differences were found to associate gender with hypomineralization of the children (p=0.512). An association between MIH with children age was found (p=0.004). Conclusions: Children with MIH require immediate treatment after the eruption of the first molars and / or incisors that exhibit high sensitivity, post eruptive fractures and rapid progression of caries lesion. This disease has a high prevalence in patients sampled. The study serves to implement preventive and restorative measures necessary.